Efecto del uso del ácido tranexámico en los valores de hemoglobina en puérperas inmediatas en el posparto vaginal, ensayo clínico aleatorizado - Vega Ortiz, Dante Alfredo (2026)
Objective: To compare prepartum and postpartum hemoglobin values in anemic pregnant women who were administered tranexamic acid with those who did not receive this medication. Methods: This is a controlled clinical trial conducted at the Honorio Delgado Hospital in Arequipa, at 2335 meters above sea level. Two groups of 30 pregnant women were randomly selected. The experimental groupreceived tranexamic acid at a dose of 1 g diluted in 10 cc immediately after cordclamping, and the control group did not receive tranexamic acid. Hemoglobin levels were determined in both groups before delivery and 4 to 6 hours after delivery.The chi-square test, Student's t-test, or Mann-Whitney test was used depending on the normality of the numerical data. Results: The pregnant women were similar in age and parity (p > 0.05). Hemoglobin values were similar before delivery, with an average value of 9.90 ± 0.99 g/dL in the experimental group and 9.97 ± 0.88 g/dL in the control group (p > 0.05). After delivery, a significantly lower value was found in the control group (8.42 ± 1.26 g/dL) than in the experimental group (9.06 ± 1.22 g/dL;p < 0.05). In the group receiving tranexamic acid, there was a decrease of 0.84 ± 0.64 g/dL in hemoglobin, while in the control group the decrease was significantly greater (1.55 ± 0.96 g/dL; p < 0.05). Conclusion: In the group of anemic pregnant women who received tranexamic acid, a smaller decrease in postpartum hemoglobin values was observed.